Ethical Issues in the Design and Conduct of Pragmatic Cluster Randomized Trials in Hemodialysis Care: An Interview Study With Key Stakeholders. (October 2020) - Nicholls, Stuart G.; Carroll, Kelly; Weijer, Charles; Goldstein, Cory E.; Brehaut, Jamie; Sood, Manish M.; Al-Jaishi, Ahmed; Basile, Erika; Grimshaw, Jeremy M.; Garg, Amit X.; Taljaard, Monica
Background: Pragmatic cluster randomized trials (CRTs) offer an opportunity to improve health care by answering important questions about the comparative effectiveness of treatments using a trial design that can be embedded in routine care. There is a lack of empirical research that addresses ethical issues generated by pragmatic CRTs in hemodialysis. Objective: To identify stakeholder perceptions of ethical issues in pragmatic CRTs conducted in hemodialysis. Design: Qualitative study using semi-structured interviews. Setting: In-person or telephone interviews with an international group of stakeholders. Participants: Stakeholders (clinical investigators, methodologists, ethicists and research ethics committee members, and other knowledge users) who had been involved in the design or conduct of a pragmatic individual patient or cluster randomized trial in hemodialysis, or their role would require them to review and evaluate pragmatic CRTs in hemodialysis. Methods: Interviews were conducted in-person or over the telephone and were audio-recorded with consent. Recorded interviews were transcribed verbatim prior to analysis. Transcripts and field notes were analyzed using a thematic analysis approach. Results: Sixteen interviews were conducted with 19 individuals. Interviewees were largely drawn from North America (84%) and were predominantly clinical investigators (42%). Six themes were identified in which pragmatic CRTs in hemodialysis raise ethical issues: (1) patients treated with hemodialysis as a vulnerable population, (2) appropriate approaches to informed consent, (3) research burdens, (4) roles and responsibilities of gatekeepers, (5) inequities in access to research, and (6) advocacy for patient-centered research and outcomes. Limitations: Participants were largely from North America and did not include research staff, who may have differing perspectives. Conclusions: The six themes reflect concerns relating to individual rights, but also the need to consider population-level issues. To date, concerns regarding inequity of access to research and the need for patient-centered research have received less coverage than other, well-known, issues such as consent. Pragmatic CRTs offer a potential approach to address equity concerns and we suggest future ethical analyses and guidance for pragmatic CRTs in hemodialysis embed equity considerations within them. We further note the potential for the co-creation of health data infrastructure with patients which would aid care but also facilitate patient-centered research. These present results will inform planned future guidance in relation to the ethical design and conduct of pragmatic CRTs in hemodialysis. Trial Registration: Registration is not applicable as this is a qualitative study.